2022
DOI: 10.3389/fendo.2022.799872
|View full text |Cite
|
Sign up to set email alerts
|

Receptors of Advanced Glycation End Product (RAGE) Suppression Associated With a Preserved Osteogenic Differentiation in Patients With Prediabetes

Abstract: Type 2 diabetes is widely documented for osteogenic differentiation defect and impaired bone quality, which is related to the skeletal accumulation of advanced glycation end products (AGEs). Prediabetes is a condition in which hyperglycemia is lower than the threshold for the diagnosis of diabetes. Prediabetic animal models consistently demonstrate impaired osteogenic differentiation and deteriorated bone microarchitecture. However, no evidence shows defects in osteoblast development and skeletal effects of AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Valenti et al 33 showed the expression of multiple osteoblast-specific genes during differentiation of the PBMC, including COL1A1 and RUNX2, and also the production of osteocalcin, the protein encoded by BGALP. Our previous studies also demonstrated the osteogenic differentiation of the PBMC-isolated from both non-diabetic and diabetic individuals 22,23,36 . To obtain the necessary stem cells in the least invasive measure, we used the PBMCisolated from participants as the source of osteoprogenitor cells in this study.…”
mentioning
confidence: 62%
“…Valenti et al 33 showed the expression of multiple osteoblast-specific genes during differentiation of the PBMC, including COL1A1 and RUNX2, and also the production of osteocalcin, the protein encoded by BGALP. Our previous studies also demonstrated the osteogenic differentiation of the PBMC-isolated from both non-diabetic and diabetic individuals 22,23,36 . To obtain the necessary stem cells in the least invasive measure, we used the PBMCisolated from participants as the source of osteoprogenitor cells in this study.…”
mentioning
confidence: 62%
“…For example, in adults with overt T2D, greater levels of AGEs in the skin correlated significantly with lower BMSi ( r = -0.30, P < 0.001) [34]. Further pointing to a potential role of AGEs is a study showing that suppression of receptors of advanced glycation end products (RAGE) in peripheral blood mononuclear cells (PBMCs) collected from prediabetic individuals was associated with preserved osteogenic differentiation potential [35 ▪ ].…”
Section: Prediabetes and Bonementioning
confidence: 99%